From irreversible to reversible covalent inhibitors: Harnessing the andrographolide scaffold for anti-inflammatory action (vol 204, 112481, 2020) - Tran, Quy TN (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2022)
10.1016/j.ejmech.2020.112943